A new airfield lighting system network architecture - Derraa, Amine; Ouaaline, Najat; Nassiri, Boujemaa (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Airport navigation lights are essential for safe night and adverse weatherflying. Airfield ground lighting (AGL) systems providevisual guidanceduring airport operations. These systems use multiple lamps connected inseries with constant current regulators (CCRs) to provide power. Promptdetection and location of failed lamps are critical to airport efficiency andcost savings. Local area network (LAN) communication facilitates lampmonitoring and control, improving system performance and reducingmaintenance costs. Effective transmission media are critical for systemreliability and efficiency. This article presents a new network architecturefor AGL systems that connects lamps and the control system using a newintelligent module; this architecture combines star and bus topologies in ahybrid intranet network. The obtained results show excellent networkingperformances by means oflatency and throughput. This architectureimproves operational efficiency and reduces maintenance for AGL systems.